Poverty Alleviation Program in Agricultural Sector: Lessons Learned and Issues - Fawzia Sulaiman (Forum penelitian Agro Ekonomi, 1998)
EnglishPoverty alleviation program in agricultural sector was initiated by an income generating program for small farmers and fishers/P4K project in 1979, and subsequently followed by various sub sectoral projects. A series of studies conducted by the Center for Agro-Socio-Economic Research on the performance and achievement level of poverty alleviation projects within agricultural sector indicated the following common features: (1) Except for the P4K and the Food and Nutrition projects, a strong sub sectoral and top-down approach was common in the project implementation. This project approach neither adequately accommodate needs and aspirations of project participants nor an effective coordination within agricultural sector and inter-sectoral coordination; (2) A too short project duration that did not accommodate community empowerment process. Community empowerment and program sustainability, which are supposed to be the main goals of a poverty alleviation program, were not adequately addressed. In the project implementation, the objective was emphasized in achieving physical project targets set in the Project Budgetary System (Daftar Isian Proyek); (3) In general, the project preparation and technical field supervision were not adequate; (4) The provision and distribution of project package were not carried out in professional manners that had resulted of the low quality of package; 5) The low capability of project participants to evolve the project package. In term of the physical achievement, the sub-sectoral poverty alleviation projects had relatively resulted of economic multiplier effects in the project areas. IndonesianProgram penanggulangan kemiskinan pada sektor pertanian dimulai pada tahun 1979 melalui proyek pengembangan penigkatan pendapatan petani-Nelayan Kecil ( proyek P4K ) yang kemudian disusul oleh berbagai proyek penanggulangan kemiskinan oleh keempat subsektor lingkup pertanian. Serangkaian penelitian yang dilakukan oleh Pusat Penelitian Sosial Ekonomi Pertanian mengenai kinerja dan tingkat pencapaian tujuan berbagai proyek penanggulangan kemiskinan di lingkup sektor pertanian mendapatkan beberapa kesamaan dalam kinerja proyek, antara lain: (1) kecuali proyek P4K dan Diversifikasi Pangan dan Gizi, sebagian besar proyek berorientasi subsektoral dengan pendekatan dari atas ke bawah. pendekatan ini kurang mengakomodasi berjalannya koordinasi yang efektif antar subsektor dan lintas sektoral,serta kurang tersalurnya aspirasi dan kebutuhan partisipan proyek; (2) Jangka waktu proyek yang terlalu singkat tidak memungkinkan diakomodasinya proses pemberdayaan masyarakat. Selain itu, pemberdayaan masyarakat dan kesinambungan program yang seharusnya merupakan tujuan utama proyek penanggulangan kemiskinan kurang memperoleh perhatian. Pencapaian tujuan proyek lebih ditekankan pada target fisik yang ditetapkan dalam Daftar Isian Proyek (DIP). (3) Persiapan proyek dan pembinaan peserta proyek kurang memadai; (4) Pengadaan serta distribusi paket proyek belum ditangani secara profesional sehingga sering dijumpai rendahnya kualitas paket proyek; (5) Kurangnya kemampuan peserta proyek dalam pengembangan peket bantuan